A Three‐State System Based on Branched DNA Hybrids. Issue 18 (21st February 2018) - He, Shiliang; Richert, Clemens
Abstract: There is a need for materials that respond to chemical or physical stimuli through a change in their structure. While a transition between water‐soluble form and solid is not uncommon for DNA‐based structures, systems that transition between three different states at room temperature and ambient pressure are rare. Here we report the preparation of branched DNA hybrids with eight oligodeoxycytidylate arms via solution‐phase, H ‐phosphonate‐based synthesis. Some hybrids assemble into hydrogels upon lowering the pH, acting as efficient gelators at pH 4–6, but can also transition into a more condensed solid state form upon exposure to divalent cations. Together with the homogeneous solutions that the i ‐motif‐forming compounds give at neutral pH, three‐state systems result. Each state has its own color, if chromophores are included in the system. The assembly and gelation properties can be tuned by choosing the chain length of the arms. Their responsive properties make the dC‐rich DNA hybrids candidates for smart material applications. Abstract : Solutions of branched oligonucleotide hybrids form gels or solids, depending on the chemical stimulus, and the transitions can be detected optically.